An evaluation of antagonist enamel wear opposing full-coverage zirconia crowns versus other ceramics full-coverage crowns and natural enamel - An umbrella review - Naisargi Shah; Harshada Nerkar; Praveen Badwaik; Bhavna Ahuja; Rahul Malu; Nikhil Bhanushali (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this umbrella review was to systematically review the systematic reviews on antagonist enamel wear opposing zirconia crowns compared to other ceramics and natural enamel. Settings and Design: This was an umbrella review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Materials and Methods: An electronic search of PubMed, Cochrane Central, EBSCOhost, and Google Scholar search engines for articles published from January 1, 2013, to January 1, 2023, was conducted using keywords "enamel wear," "zirconia," "feldspathic," "dental ceramics," and "Y-TZP" to identify systematic reviews on antagonist enamel wear opposing zirconia crowns compared to other ceramics and natural enamel. Statistical Analysis Used: Qualitative analysis. Results: A total of 86 articles were obtained through electronic search, of which four articles were selected after abstract screening that met the inclusion criteria for evaluating antagonist enamel wear. As compared to feldspathic groups, zirconia had substantially less antagonist wear, while surface polishing exhibited less enamel wear than glazing. Because of the heterogeneity in study design, measurement methods, and outcome variables, a meta-analysis was not possible. Conclusions: Over time, the opposing enamel wear caused by polished monolithic zirconia will be either equal to or less than that of natural enamel wear. Polished monolithic zirconia also maintains lower values of enamel wear compared to metal ceramics, feldspathic porcelains, and lithium disilicate.